(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Pneumatic actuators offer several advantages over electromechanical and hydraulic actuators for positioning applications. However, pneumatic actuators subjected to high frictional forces, dead zone and dead time, making it difficult to achieve fast and precise position control. This research paper presents the process of identifying design, modeling, and controllers for the pneumatic actuator control system. Three-position pneumatic cylinder is the solution to all problems that occur because of two pneumatic two-position slides. Different external loads are added to investigate the effectiveness of the controllers designed in the system in real time. The performance monitoring of the closed circuit system is satisfied and offers considerable resistance even at a slight increase in load.